Characterization of Intracellular Reverse Transcription Complexes of Moloney Murine Leukemia Virus - Fassati, Ariberto (American Society for Microbiology, 1999)
To examine the early events in the life cycle of Moloney murine leukemia virus (MoMLV), we analyzed the intracellular complexes mediating reverse transcription. Partial purification of the reverse transcription complexes (RTCs) by equilibrium density fractionation and velocity sedimentation indicated that three distinct species of intracellular complexes are formed shortly after cell infection. Only one of these species is able to start and complete reverse transcription in the cell cytoplasm. This RTC is composed of at least the viral genome, capsid, integrase, and reverse transcriptase proteins. The RTC becomes permeable to micrococcal nuclease but not to antibodies. Shortly after initiation of reverse transcription, the viral strong stop DNA within the RTC is protected from nuclease digestion. The sedimentation velocity of the RTC decreases during reverse transcription. After entry into the nucleus, most capsid proteins are lost from the RTC and its sedimentation velocity decreases further.